The reliability and validity of malay version of Fear Avoidance Beliefs Questionnaires (FABQ) among low back pain suffers: a pilot study/ Zarina Zahari, Nor Azizah Ishak & Maria Justine - Zahari, Zarina; Ishak, Nor Azizah; Justine, Maria (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Fear-avoidance beliefs is well known to affect disability, work loss and physical activities in back pain patient and become an important aspect to be assessed. The purposes of this study were to describe the process used to translate the Malay version of FABQ (MFABQ) and to determine the test-retest reliability and validity of the MFABQ among Malay-speaking low back pain (LBP) patients. The MFABQ was translated by using forward and back-translated method following WHO recommendation. The MFABQ was tested among 60 patients with LBP for the reliability and validity purposes. The test-retest within a two-day interval was performed by assessing the intraclass correlation coefficient. The construct validity was assessed with correlation between the MFABQ and the SF-36v2 by using Pearson correlation coefficients. The results showed the test-retest reliability was good with the intraclass correlation coefficient value 0.831 for the total score of MFABQ. The construct validity of MFABQ showed that this questionnaire was valid. The fear avoidance beliefs physical work test and retest were inversely correlated with the mental scales of the SF-36 (r=0-.407) and (r=-0.345) respectively. The reliability and construct validity of the MFABQ were acceptable for assessing fear-avoidance beliefs of Malay speaking patients with LBP.